PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN REAL ESTATE - Somally, Monica Chen; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research aims to analyze the effect of liquidity, leverage, and profitability, as well as firm size on the possibility of financial distress with the Altman approach in property and real estate companies listed on the Indonesia Stock Exchange during 2019-2021. The sample was selected using purposive sampling method. The valid data amounted to 24 companies. Multiple regression analysis was used as the data processing technique assisted through EViews version 12 and Microsoft Excel 2016 programs. The results showed that leverage has a positive effect on financial distress and profitability has a negative effect on financial distress. The implication of this research is that companies should pay attention to financial performance such as the amount of debt to the profits generated so that companies can realize early the possibility of financial distress.